(3GdfaS GdjeGfi hGdQhM GdQhMGfi (B( (3aj ELGRI GdbVGI Hfi GdThcGfi (B)s - (3YHO GdQMef Hf SdjeGf Hf jMji Hf YeQ Hf ebHhd GdGgOd,J (B13 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hGdTcQ ddg eG TGA Gddg hdG bhI EdG HGddg CeG HYO , adeG cGf WdH GdELGRI ef GdCYdi hGdeSGhi hGdOhf WQjbI s
(3BNQgG (B:s
(3bGd dbefi QShd Gddg Udi Gddg Ydjg hidg hSde EfgJgi GdeQGO fbdg Je Pdc HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs